Міжнародна академічна мобільність в умовах інтернаціоналізації освіти - Гуткевич, Світлана Олександрівна; Сидоренко, Павло Олександрович (My University, 2023)
В статті розглянуто теоретичні засади освітнього туризму на основі аналізу міжнародної академічної мобільності. Міжнародна академічна мобільність розглядається як складова розвитку науково-освітньої галузі, яка також має істотний вплив на загальний соціально-економічний поступ. Розглянуто питання, в зв’язку зі зростанням чисельності іноземних студентів, конкуренції між приймаючими країнами. Міжнародний освітній туризм є одним із проявів академічної мобільності. В процесі дослідження було визначено основні тенденції розвитку освітнього туризму в умовах інтернаціоналізації освіти. Проаналізовано також передумови та чинники розвитку освітнього туризму і виділено основні принципи стимулювання його розвитку. This article analyzes the theoretical foundations of educational tourism based on the analysis of international academic mobility. International academic mobility is considered as a component of the development of the scientific and educational industry, which also has a significant impact on the general socio-economic progress. International educational tourism is one of the manifestations of academic mobility. In the process of research, the main trends in the development of educational tourism in the context of the internationalization of education were determined. This article also analyzes different approaches to the definition of educational tourism and examines the essence of this phenomenon. Educational tourism is defined as trips with an educational purpose lasting from overnight stay to one year, which may be accompanied by recreational activities. A classification of educational tourism by objectives, age of travelers, and stages of their career development is proposed. Educational tourism is considered as a complex, interdisciplinary phenomenon, which is demonstrated with the help of the graphic model "MET: Mobility, Education, Tourism". The proposed approach to the classification of types of educational mobility according to the objectives and duration of stay in the host country made it possible to distinguish between day visits, tourism, other types of educational mobility, temporary educational migration, and migration. The prerequisites and factors of the development of educational tourism are also analyzed, and the main principles of stimulating its development are highlighted, in particular, the application of the concept of the lifetime value of the client, i.e., taking into account the value of each visitor in the long term.
Keywords: інтернаціоналізація освіти; освітній туризм; освітні програми; освітні інновації; educational tourism; educational migration; academic tourism; scientific and educational tourism; educational mobility; кафедра міжнародної економіки